Gambaran Histopatologi Kulit Anjing Penderita Dermatitis (HISTOPATHOLOGICAL FEATURES OF DOG’S SKIN WITH DERMATITIS) - Purnama, Komang Andika; Winaya, Ida Bagus Oka; Adi, Anak Agung Ayu Mirah; Erawan, I Gusti Made Krisna; Kardena, I Made; Suartha, I Nyoman (Jurnal Veteriner; Vol 20 No 4 (2019), 2019)
Complex dermatitis is a disorder of the skin caused by the combination of several agents such as fungi, ectoparasites, bacteria, and metabolic diseases with combined clinical symptoms of primary lesions and secondary lesions. This study aims to determine the histopathology of dog skin with complex dermatitis. There were 15 samples of dogs with complex dermatitis, skin biopsy and histopathology. The results showed that the incidence of complex dermatitis in young dogs was 60%, long-haired 67%, male sex 73%, and domestic race 73%. Macroscopic examination found a change in hyperkeratosis. Microscopically observed that infiltration of polymorphonuclear cells, monomorphonuclear cells and macrofag from moderate to severe in the dermis. In hair follicles and epidermis occured akantosis, and keratin proliferation. There were segment fragments from infectious agents such as Demodex canis, Sarcoptes scabiei, and yeast from Malasezia sp. Other changes were observed in the presence of hydrophic degeneration, necrosis, and ulcers. Dogs suffering from complex dermatitis have chronic infections with more than one infectious agent. Disabilities based on histopathological observation of dogs with complex dermatitis with moderate severity of 33%, and severe 67%.